Need for treatment in all skeletal class III cases – a dilemma? a case report - Mahajan, Monika (International Journal of Dental Research, 2017)
Skeletal malocclusion affects dental and facial tissues. A complicating factor for diagnosis and treatment of skeletal class III malocclusion is its multifactorial etiology. Genetics play an important role in determining the facial morphology of an individual. Prediction of a skeletal class III based on morphology can play an important step in orthodontic diagnosis and treatment planning. This case report further supports the significant role of genetics in skeletal class III malocclusion. As seen in our case the skeletal class III if left untreated does not detiorate but rather shows a decrease in ANB ie in anterioposterior discrepancy. Hence the need for treatment should be analysed thoroughly in skeletal class III patients.